Quality of Context in Context-Aware Systems - A.Q. Al-Shargabi, Asma; Siewe, Francois; T. Zahary, Ammar (EAI Endorsed Transactions on Context-aware Systems and Applications, 2017)
Context-aware Systems (CASs) are becoming increasingly popular and can be found in the areas of wearable computing, mobile computing, robotics, adaptive and intelligent user interfaces. Sensors are the corner stone of context capturing however, sensed context data are commonly prone to imperfection due to the technical limitations of sensors, their availability, dysfunction, and highly dynamic nature of environment. Consequently, sensed context data might be imprecise, erroneous, conflicting, or simply missing. To limit the impact of context imperfection on the behavior of a context-aware system, a notion of Quality of Context (QoC) is used to measure quality of any information that is used as context information. Adaptation is performed only if the context data used in the decision-making has an appropriate quality level. This paper reports an analytical review the state of the art on quality of context in context-aware systems and points to future research directions.